The ECtHR’s Ilias and Ahmed and the CJEU’s FMS-case: a difficult reconciliation? - Anne Bombay; Pieterjan Heynen (sui-generis)
Recently, two important judgments concerning detention in European Asylum law were issued: the Ilias and Ahmed case of the ECtHR and the FMS-case of the CJEU. Both Courts had to decide on the question whether the situation of asylum seekers in the Hungarian Röszke transit zone amounted to detention. Notwithstanding the similar facts of the cases, no violation of Article 5 ECHR was found by the ECtHR, whereas the CJEU clearly condemned Hungary for its violation of EU Asylum Law. This raises questions concerning the reconcilability and long-term effects of the two judgments.